2009
DOI: 10.1002/jsfa.3820
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of growth, fermentative efficiency and ethanol tolerance of Kloeckera africana during the fermentation of Agave tequilana juice by addition of yeast extract

Abstract: This study revealed the importance of supplementing A. tequilana juice with a convenient N source to achieve fast and complete conversion of sugars in ethanol, particularly in the case of K. africana. This yeast exhibited similar growth and fermentative capacity to S. cerevisiae. The utilisation of K. africana in the tequila industry is promising because of its variety of synthesised aromatic compounds, which would enrich the attributes of this beverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…In tequila production, yeast extract has been reported to stimulate the growth, fermentative capacity and alcohol tolerance of K. africana. In fact, when K africana fermentation was supplemented with yeast extract, maximum specific growth rate (l max ), ethanol production and sugar consumption reached similar values to those calculated for S. cerevisiae cultured in agave juice supplemented with ammonium sulfate (Díaz-Montaño et al 2010). When the fermentation medium was supplemented with asparagine, K. africana showed a fermentative capacity similar to that obtained using yeast extract.…”
Section: Study Of the Amino-acids Preference Of K Africanasupporting
confidence: 69%
See 2 more Smart Citations
“…In tequila production, yeast extract has been reported to stimulate the growth, fermentative capacity and alcohol tolerance of K. africana. In fact, when K africana fermentation was supplemented with yeast extract, maximum specific growth rate (l max ), ethanol production and sugar consumption reached similar values to those calculated for S. cerevisiae cultured in agave juice supplemented with ammonium sulfate (Díaz-Montaño et al 2010). When the fermentation medium was supplemented with asparagine, K. africana showed a fermentative capacity similar to that obtained using yeast extract.…”
Section: Study Of the Amino-acids Preference Of K Africanasupporting
confidence: 69%
“…K. africana showed the highest biomass production (6.18 g/l) when supplemented with asparagine. It is important to mention that this biomass concentration represents the highest value ever reported for this yeast genus in alcoholic fermentation (Díaz-Montaño et al 2008, 2010. Good biomass production was also obtained with yeast extract (3.38 g/l), glutamine (3.35 g/l) and arginine (3.09 g/l) (Fig.…”
Section: Study Of the Amino-acids Preference Of K Africanamentioning
confidence: 57%
See 1 more Smart Citation
“…28 It was also shown that better growth, reducing sugar consumption and ethanol tolerance for Kloeckera africana cultures supplemented with yeast extract compared with those supplemented with ammonium sulfate. 29 When glycine was not added to the medium, methanol produced in the medium supplemented with 12.5 g L −1 yeast extract was 29.9 mg L −1 more than that produced in the medium without yeast extract (Fig. 5A).…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, in anaerobic conditions, the dominant mode is fermentation. Saccharomyces cerevisiae, through the Crabtree effect, is one of the few yeasts able to grow well in either aerobic or anaerobic conditions, with fermentation in both cases as long as the sugar concentration is not Identifying yeast isolated from spoiled peach puree and assessment of its batch culture for invertase production (Díaz-Montaño et al, 2010;Nevoigt, 2008). When glucose is below a critical concentration, between 0.09 and 0.9% in mass, it favors diauxic growth onset and the yeast may have both growth profiles, the second of which is followed by the consumption of another non-fermentable carbon source in the medium, usually ethanol aerobically.…”
Section: Introductionmentioning
confidence: 99%